Fast charger for Li-ion batteries based on battery temperature - Hadi A.; Said I.; Mansor M.; Hussain H. (Institution of Engineering and Technology, 2023)
A fuzzy controlled fast charger for Lithium Ion (Li-ion) batteries based on battery temperature is investigated and simulated by using MATLAB/Simulink. The main objective of this study is to control temperature rise during fast charging. A fuzzy control system is applied to a DC-DC converter that functions as a battery charger. During the charging process, battery temperature and battery state-ofcharge (SOC) were used as controller input variables and charging current as output variable. The battery is charged at 3C charging rate from 0% to 80% SOC. The simulation result is compared with the Constant-Current Constant-Voltage (CC-CV) charging algorithm and analysed. According to the simulation result, the proposed charger is capable of charging li-ion battery with reduced rate of temperature rise.